Abordagem de recomendação baseada em conteúdo utilizando ontologia fuzzy de domínio e ontologia crisp de preferência do usuário - Baldárrago, Arturo Elias Urquizo (2012)
This paper presents an approach for developing content-based recommendation applications with focus on the use of a specific domain fuzzy ontology along with a user preference ontology. The approach falls into two stages: Ontology Engineering and Recommendation System Engineering. In the Ontology Engineering, a domain ontology with fuzzy relationships and a user ontology are built. The user ontology is set as an instance of the domain ontology, but it is modeled in a way that allows to store each user s preferences. The usage of the ontologies produced in Ontology Engineering provides a gain in precision for the results obtained by applications in the Recommendation System Engineering stage. For evaluation purposes, we instantiated the proposed approach in the development of a Recommender System for the field of electronic commerce, focusing on the mobile devices commerce domain. Following the experimental methodology, An evaluation was conducted in order to assess the approach s impact on the accuracy of results provided by the developed Recommender System. The results showed that the use of our approach contributed to increase the accuracy of the results, in terms of prediction, classification and ranking. The contributions of this work include: the approach for developing content-based recommendation applications by using a specific domain fuzzy ontology along with a user preference ontology; the definition of the UPFON methodology, which integrates the approach, to construct fuzzy ontologies; an instantiation of a fuzzy ontology for the mobile devices domain and a strategy to capture; and propagate the user preferences by means of ontologies.